Entrepreneurship-Based Management Program as An Effort to Improve The Quality of Non-Formal Educational Institutions - Cahyani, Arini Dwi; Suminar, Tri; Arbarini, Mintarsih; Rusdi, Firman Maulana (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2025)
The management of the Community Learning Activity Center (CLC) institution is low, making some people less enthusiastic about participating in the program’s implementation. CLC is an institution, a forum, and a place to serve the community’s learning needs. Entrepreneurship encourages people to be enthusiastic about learning. The purpose of this study is to examine and describe entrepreneurship-based program management as an improvement in the quality of non-formal educational institutions.. This study uses a qualitative approach with a survey: data collection techniques, in-depth interviews, participatory observation, and documentation. The research subjects are administrators, tutors, and learning residents. They use qualitative analysis techniques with data reduction steps, data display, data verification to conclude. The results showed that the development of the CLC program followed the following steps: identification of learning needs, determining learning priorities, involving community leaders in planning program planning, considering local potential and local wisdom; and empowerment programs based on entrepreneurship, compiling programs to produce superior products as program sustainability, managers work professionally to make CLC independent in each program, and open networks with business partners for select marketing products.